IMPLEMENTASI KERJASAMA SISTER CITY KOTA BANDUNG DAN KOTA SEOUL TAHUN 2018 - 2020 - Ria Hani Saputri; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The research was conducted to understand how the two actors of the nation state, in this case the City of Bandung and the City of Seoul, cooperate in various ways to increase the capacity of their respective regions in multi-sectors. Sister City or sister/twin city is a collaboration that has been built by the two actors. The research was made based on the theory of paradiplomacy, in the level of analysis of the nation state to understand the implementation of a cooperation that was agreed upon by the collaborating actors. Data collection was carried out using qualitative research methods, with data sourced from the official website for the Regional Cooperation with Overseas Bandung City, the Korea-Seoul Metropolitan City site, books, and journals that discussed issues related to sister city cooperation, especially sister cities by the two actors, namely Bandung and Seoul. The results of this paper show that it is comparable to the hypothesis that was developed where the implementation of the sister city cooperation is going well. This is seen from the good implementation of the Seoul Metropolitan Government Employee Apprenticeship Program in the Bandung City Government, Facilitating the Opening of Little Bandung Wall in Seoul City, and Revitalizing the Cikapundung River. Keywords: Bandung City, Seoul, Paradiplomacy, Sister City.